Desigualdad y pobreza en el Gran La Plata : Condiciones de vida en el Barrio José Luis Cabezas, Ensenada 2016 - Eguía, Amalia (Dir.); Rausky, María Eugenia (Dir.); Ortale, Susana (Dir.) (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación, 2023)
This report presents the results of the census survey carried out in the José Luis Cabezas neighborhood during the months of October and November 2016.